Association of Plasma and Electroencephalography Markers With Motor Subtypes of Parkinson’s Disease - Yang, Xiaoxia; Li, Zhen; Bai, Lipeng; Shen, Xiao; Wang, Fei; Han, Xiaoxuan; Zhang, Rui; Li, Zhuo; Zhang, Jinghui; Dong, Mengmeng; Wang, Yanlin; Cao, Tingyu; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: The aim of our present study is to investigate the correlations of plasma neurodegenerative proteins and electroencephalography (EEG) dynamic functional network parameters with disease progression in early Parkinson’s disease (PD) with different motor subtypes, including tremor-dominant (TD) and postural instability and gait disorder (PIGD). Methods: 33 PD patients (21 TD and 12 PIGD) and 33 healthy controls (HC) were enrolled in our study. Plasma NfL, α-syn, t-tau, Aβ42, and Aβ40 levels were measured by ultrasensitive single molecule array (Simoa) immunoassay. All the PD patients underwent EEG quantified by dynamic functional network analysis. The motor and non-motor performances were evaluated by a series of clinical assessments. Subsequently, the correlation analysis of plasma biomarkers and EEG measures with clinical scales was conducted. Results: In TD group, plasma NfL exhibited a significant association with MDS-UPDRS Ⅲ and MoCA. Higher Aβ42/40 level was significantly related to a decrease of HAMD and HAMA in PIGD group. In terms of the correlation between EEG characteristic parameters and clinical outcomes, TT delta was positively correlated with MDS-UPDRS Ⅲ and MoCA scores in TD group, especially in prefrontal and frontal regions. For other non-motor symptoms, there were significant direct associations of kPLI theta with HAMD and HAMA, especially in prefrontal region, and kPLI gamma was particularly correlated with RBDSQ scores in prefrontal, frontal and parietal regions in TD group. Furthermore, there was a significant positive correlation between plasma t-tau and kPLI and pairwise correlations were found among plasma NfL, theta TT and MoCA scores in TD group. Conclusions: These results provide evidence that plasma neurodegenerative proteins and EEG measures have great potentialities in predicting disease progression of PD subtypes, especially for TD subtype. A combination of these two kinds of markers may have a superposition effect on monitoring and estimating prognosis of PD subtypes and deserves further research in larger, follow-up PD cohorts.